The effect of offensive and defensive actions on taekwondo sparring - Wasik, J.; Pieter, W.; Borysiuk, Z. (Journal of Combat Sports and Martial Arts, 2014)
Introduction. The purpose of this study was to assess the performance of selected male (-71 kg) and female (-63 kg) taekwondo athletes competing under the rules of the International Taekwondo Federation (ITF) in terms of attacks, counter-attacks, fake attacks and fake counter-attacks. Material and methods. Subjects were participants at the 2007 Polish ITF Taekwondo Championships. A Sony digital video camera (Digital 8) was employed as well as a hand notation system to tabulate the data. The Mann-Whitney U test was used to analyze the data. Results. The winning male (ES = 0.404) and female (ES = 0.686) taekwondo athletes attacked more. There was no difference in the number of counter-attacks between successful and less successful taekwondo athletes in males (ES = 0.011) and females (ES = 0.097). Conclusions. Future research should include the specific techniques that were used as well as those that scored most.